CHARACTERISTICS OF SUGARCANE FIBER COMPOSITE REINFORCED WITH MALAPOGA WOOD COATING - Sirajuddin, Awal Syahrani; Fadly, Muhammad Syaiful; Iqbal, Muhammad; Asmara, Anjar (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Rapid technological developments have led to an increased demand for composite materials. However, composite materials utilizing natural fibers, such as sugarcane bagasse fiber, have not been fully optimized. This study aimed to analyze the characteristics of sugarcane bagasse fiber-reinforced composites with a Malapoga wood coating, focusing on the Modulus of Elasticity (MOE) and Modulus of Rupture (MOR). The primary material used in this research was Malapoga wood (Toona Ciliata M. Roem), which was treated with a mixture of sugarcane bagasse fiber and epoxy in volume ratios of 30%:70%, 40%:60%, and 50%:50%. The composites were then coated with Malapoga wood under cold pressure. Specimens and bending strength testing procedures followed ASTM D143 standards. Macro photographs of the fracture cross-sections of the test specimens were taken to determine the failure mechanism. The test results indicated that the composite with a 50%:50% composition exhibited highest MOE and MOR values compared to the other compositions. The maximum modulus of elasticity (MOE) at 50% was 70,256.67 kg/cm², and for 50% MOR, it was 716.36 Kg/cm². The mixture of sugarcane bagasse fiber with epoxy produced a denser coating on the Malapoga wood.